A virtual assessment of the suprainiac depressions on the Eyasi I (Tanzania) and Aduma ADU-VP-1/3 (Ethiopia) Pleistocene hominin crania. Issue 145 (August 2020) - Bosman, Abel Marinus; Reyes-Centeno, Hugo; Harvati, Katerina
Abstract: Despite a steady increase in our understanding of the phenotypic variation of Pleistocene Homo, debate continues over phylogenetically informative features. One such trait is the suprainiac fossa, a depression on the occipital bone above inion that is commonly considered an autapomorphy of the Neanderthal lineage. Challenging this convention, depressions in the suprainiac region have also been described for two Pleistocene hominin crania from sub-Saharan Africa: Eyasi I (Tanzania) and ADU-VP-1/3 (Ethiopia). Here, we use a combined quantitative and qualitative approach, using μCT imaging, to investigate the occipital depressions on these specimens. The results show that neither the external nor the internal morphologies of these depressions bear any resemblance to the Neanderthal condition. A principal component analysis based on multiple thickness measurements along the occipital squama demonstrates that the relative thickness values for the internal structures in Eyasi I and ADU-VP-1/3 are within the range of Homo sapiens . Thus, our results support the autapomorphic status of the Neanderthal suprainiac fossa and highlight the need to use nuanced approaches and multiple lines of evidence.